REACCION DE WIDAL EN PERSONAS NO FEBRILES - VARELA; HITZ (Rockefeller Foundation, CD MEXICO, DF, MEX, 1944)
An increase in number of cattle, sheep, hogs and goats in 1937 over 1930 is vividly shown for the country, and the status of livestock for each of the 5 livestock zones is given Also grazing and the deferred rotation method of pasturing should help maint
REV MEX MED
Keywords: REACCION, WIDAL, PERSONAS, FEBRILES; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA